Acts of Agency: Exploring a Feminist Approach to Abortion Research in Sri Lanka. (September 2020) - Wijesiriwardena, Subha; Silva, Kimaya de; Divakalala, Cayathri; Issadeen, Hasanah Cegu
In Sri Lanka, abortion continues to be a criminal offence under the Penal Code of 1883. Several attempts have been made to challenge the colonial-era law since the 1990s with no success thus far. This study documents and centres the knowledge of women and transpersons in accessing abortion and sexual health and reproductive health services in Sri Lanka in order to contribute to the conversation on abortion law reform as well as research and advocacy. Our data suggest that the existing legal reforms proposed to the abortion law would be unresponsive to the needs of women and transpersons in Sri Lanka, and that in additional to legal changes, we would need significant social and cultural changes. This study uses feminist research methodologies, building towards a feminist ethics in abortion research.